High-throughput NMR-based metabolomics: a robust toolbox for searching human disease biomarkers / Syed Adnan Ali Shah - Ali Shah, Syed Adnan (Faculty of Pharmacy, 2024)
Metabolomics deals with the whole ensemble of metabolites (the metabolome). It is a holistic approach to studying systematic metabolic changes in biospecimens such as cells, tissue, organs, or organisms. It is a valuable tool that uniquely connects all "omics" techniques and best represents the phenotype. As one of the -omic sciences, it relates to biology, physiology, pathology and medicine, but metabolites are chemical entities, small organic molecules or inorganic ions. Therefore, their proper identification and quantitation in complex biological matrices require a solid chemical ground [1]. Metabolomics monitors the global outcome of all exogenous and endogenous factors without making assumptions about the effect of any single contribution to that outcome. It makes metabolomics a perfect technique for investigating and understanding the molecular mechanisms of human health and disease.